2021
DOI: 10.4102/sajce.v11i1.700
|View full text |Cite
|
Sign up to set email alerts
|

Foundation phase pre-service teachers’ experiences of teaching life skills during teaching practice

Abstract: Background: In South Africa socio-economic problems such as poor health conditions, juvenile delinquency, high rates of school dropout and teenage pregnancy are increasing. Therefore, it is vital to prepare foundation phase (FP) pre-service teachers to fortify children with basic life skills (LS) that will help them to cope with real-world challenges and demands.Aim: The study is aimed to explore the experiences of pre-service FPLS teachers during their teaching practice.Setting: This qualitative case study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…That is, what they met during their teaching practice had no relationship with the knowledge they acquired in the university, especially, the educational theories learnt. This finding agrees with a study that reported similar results where student-teachers on teaching practices lamented the difficulty they experienced in implementing Life Sciences curriculum due to the disparity in the knowledge acquired and that which was required (Arasomwan & Mashiya, 2021). In a similar study conducted at the University of Limpopo, it was also reported that in some areas, teaching practice students found little connection between what they were taught in the university and what they were expected to implement during the exercise at the place of practice (Modipane & Kibirige, 2015).…”
Section: Implementation Challengessupporting
confidence: 92%
See 1 more Smart Citation
“…That is, what they met during their teaching practice had no relationship with the knowledge they acquired in the university, especially, the educational theories learnt. This finding agrees with a study that reported similar results where student-teachers on teaching practices lamented the difficulty they experienced in implementing Life Sciences curriculum due to the disparity in the knowledge acquired and that which was required (Arasomwan & Mashiya, 2021). In a similar study conducted at the University of Limpopo, it was also reported that in some areas, teaching practice students found little connection between what they were taught in the university and what they were expected to implement during the exercise at the place of practice (Modipane & Kibirige, 2015).…”
Section: Implementation Challengessupporting
confidence: 92%
“…Amongst the chief findings of the study was the identification of a disconnection between what preservice teachers studied in the university and what they were expected to implement during teaching practice. Similarly, another study which explored the experiences of preservice Foundation Phase (FP) Life Science teachers during their teaching practice in South Africa also highlighted among others, difficulty in the implementation of FP curriculum, support from mentors and lack of awareness (Arasomwan & Mashiya, 2021). Another study was conducted in KwaZulu-Natal which explored the views of third-year student teachers' capabilities of classroom management.…”
Section: Empirical Evidence In Preservice Teacher Researchmentioning
confidence: 99%
“…Moreover, a practical micro-teaching component in teacher training programs could help pre-service teachers acquire basic teaching skills and develop self-confidence to avoid the challenges encountered by the participants in this study. Additionally, Arasomwan and Mashiya (2021) emphasized the foundation phase in pre-service teachers' experiences in teaching life skills during their teaching practice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schulleri (2020) stated that mentors gained interpersonal skills while mentees gained classroom management skills. In corroboration, Arasomwan and Mashiya (2021) stated that mentees had pleasant experiences when receiving assistance required from their mentors, for instance in the use of teaching resources for effective teaching. Some mentees reported that they had particular challenges in teaching learners in the medium of instruction (English) as mentors were mostly using the learners' home languages.…”
Section: Experiences By Mentors and Menteesmentioning
confidence: 94%